After the Arab Uprisings: resilience or transformation?. (1st March 2016) - Viola Sarnelli
Abstract : This article looks at the ongoing political changes in two non-democratic regimes moving beyond the 'authoritarian resilience' model. Five years after the Arab Uprisings, Jordan and Algeria seem to have resisted the revolutionary wave that has shaken the whole MENA region. According to the old debate informed by 'authoritarian resilience' and 'democratic transition' models, a series of obstacles in the political, economic or social sphere would prevent a successful 'transition' to democracy in some countries more than in others. Despite the criticisms addressed to the classical version of these models, they still influence most of the explanations of what happened after 2011, even though in their 'upgraded' version (Haydemann 2007; Heydemann and Leenders 2011). However, given the specific set of challenges and transformations each of the countries is going through, this framework becomes increasingly unsatisfactory. Jordan and Algeria are two profoundly diverse countries, and yet both are quite exceptional cases in their own right. Compared to other Arab monarchies, Jordan stands between the untouched authoritarian Gulf model and the constitutional reformist path followed by Morocco (Yom 2011; Yom and Gause 2012). As for Algeria, it was the only republic in the region to be apparently not affected by the regional turmoil (Volpi 2013). Still, in order to survive the 2011 protests, both regimes were forced to approve a number of 'facade' reforms. This article argues that such reforms, despite being mostly formal concessions, seen from a different angle could also be a starting point for more substantial long-term transformations. After all, does a truly "resilient" authority, elite or regime really exist?